(untitled) (Nexo Revista Científica, 2021)
The present article provides a substantiation of the need to use the potential of the philosophy of science in designing a sustainable development project. Along with mathematics and informatics, the philosophy of science is viewed as an auxiliary science designed to help clarify the conceptual and methodological nature of scientific theories. New provisions of science philosophy are presented. The proposition that all axiological theories culminate in ethics is proved. It is also substantiated that natural sciences demonstrate ethical relativity. The project, i.e. both the concept and conception (theory) of sustainable development was designed with no consideration of the achievements of science philosophy including scientific ethics. As the project developed its content became not clearer but, on the contrary, more obscured. The project of sustainable development is reevaluated in light of the philosophy of science. It turns out to be nothing more than a paraphrase of the need for the proper development of the ethical relativity of ecology and its place in the system of balanced scientific ethics. The project of sustainable development presents a paraphrase of certain scientific content that has to be properly addressed. Without this, it has no scientific meaning and should be attributed to the field of everyday language. Thus, the time to put the sustainable development project on a scientific track has come.